Archaic Greek Earrings: An Interim Survey - Castor, Alexis Q. (Archäologischer Anzeiger, 2017)
Although earrings were one of the most common jewelry types in Greece, the most recent survey of this ornament is the 1903 study by Karl Hadaczek. This study focuses on earrings discovered in controlled excavations and dating to the Archaic period; such a restriction both confirms the authenticity of the earrings and also provides insight into the occasions on which jewelry was deliberately removed from circulation by its owner. A survey of the evidence related to earrings reveals how they worn, hints that men and women may have sported the accessories and provides some clues to the manufacture of jewelry. Following this overview, a typology of Archaic earring forms based on firm regional and chronological data is provided. As jewelry is a type of wealth that we can link specifically with Greek women, study of these ornaments offers unique – and under-exploited – evidence for female participation in the public sphere.